Influence of stress towards project performance among contractors - Mohamad Ali-Hassan, Mohamad Termizi (2014)
The purpose of this research is recognize whether the stress can influence project performance. As project conditions nowadays is more challenging and mostly full of uncertainty, stress is one of common problem faced by contractors. In order to discover the effect of stress towards project performance, a survey is conducted to identify the presence of stress in a project in the first phase of the project, follow by source of stress and project performance level among a group of contractors. In this research, I will present the result of the research to prove the relationship between stress and project performance